Risk factors for healing failure after arthroscopic rotator cuff repair in small to medium-sized tears: a retrospective cohort study - Wang, Guangying; Liu, Changli; Wang, Jiansong; Li, Haoran; Yu, Guosheng (Frontiers in Surgery, 2024)
ObjectivesTo identify risk factors for tendon healing failure following arthroscopic rotator cuff repair (ARCR) in patients with small to medium-sized rotator cuff tears (RCTs).MethodsA retrospective study was conducted on 320 patients with RCTs who underwent arthroscopic repair between June 2018 and June 2021. All patients had at least 2 years of postoperative follow-up, with MRI scans at the final assessment. Based on MRI results, patients were categorized into the healing success group (Group A: types I–III) or the healing failure group (Group B: types IV–V). Variables associated with rotator cuff healing, including patient characteristics, baseline symptoms, imaging data, and surgery-related factors, were analyzed using univariate and multivariate logistic regression.ResultsHealing failure occurred in 54 of the 320 patients (16.9%). Functional status improved significantly across all patients (P < 0.05), irrespective of healing outcomes. Multifactorial analysis identified smoking (OR = 1.931, P = 0.028), diabetes (OR = 3.517, P = 0.038), lower bone mineral density (BMD) (OR = 1.551, P = 0.018), higher fatty infiltration (FI) (OR = 4.025, P = 0.009), and smaller acromiohumeral distance (AHD) (OR = 2.546, P = 0.006) as independent risk factors for healing failure.ConclusionsSmoking, diabetes, lower BMD, higher FI, and smaller AHD are independent risk factors for healing failure following ARCR.